STRATEGIES AND TECHNIQUES IN TRANSLATING ENGLISH MOVIE TITLES INTO VIETNAMESE IN MEGASTAR CINEPLEX = Chiến lược và thủ thuật trong dịch tiêu đề phim từ tiếng Anh sang tiếng Việt tại rạp chiếu phim megastar - Trần, Thị Minh (2020)
In Vietnam, together with the rapid development of the movie industry, movie translation has become a dominant aspect of translation. Aware of the importance of movie translation, quite a few international and domestic researches have investigated the issue. However, so far, movie title translation has received little attention of Vietnamese researchers. Hence, in an attempt to gain more insights into movie title translation, this research investigates the strategies and techniques that are employed in translating film titles from English into Vietnamese in Megastar Cineplex, which is regarded as the leading company in theatre business in Vietnam. This goal was achieved by both quantitative and qualitative approaches. They were respectively applied in the two phases of the study. In the first phase, document analysis method with movie titles serving as instrument was utilized to examine the strategies in translating English movie titles. In the second phase, three translators having experience of working for Megastar Cineplex were requested to participate in the face-to-face semi-structured interviews in order to investigate the process of releasing movie titles as well as the principles and techniques utilized by the participants in translating movie titles from English into Vietnamese in Megastar Cineplex. The results from both phases show that (1) seven procedures and one method were applied for translating movie titles in Megastar Cineplex from 2011 to 2012; (2) a translated title must undergo certain phases of internal and external examinations before being released in Vietnam; (3) there are five major principles to be followed the participants when translating movie titles; and (4) each translator has their own techniques to deal with movie title translation. The findings from the study hopefully will benefit not only translators who work with movie title translation but also researchers and people interested in the issue.